2003
DOI: 10.1111/1467-8624.00601
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to Understanding Mind: Construct Validity and Predictive Validity of Maternal Mind‐Mindedness

Abstract: The construct validity of maternal mind-mindedness (MM) was investigated in the context of its relations with children's later understanding of mind. MM measures were obtained from infant-mother (N = 52) interactions at 6 months, and from maternal interviews at 48 months. Children's understanding of mind was assessed using theory of mind (ToM) tasks at 45 and 48 months, and a stream of consciousness (SoC) task at 55 months. One of the early MM measures--mothers' appropriate mind-related comments--was a positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
363
8
17

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 366 publications
(417 citation statements)
references
References 38 publications
(70 reference statements)
29
363
8
17
Order By: Relevance
“…The following pathways were modelled: (a) concurrent relations between baseline HRV and HRV decline during the stranger situation at 4 and 12 months (e.g., Izard et al., 1991; Porter et al., 1995), (b) concurrent relations between appropriate or non‐attuned mind‐related comments and baseline HRV or HRV decline at 4 and 12 months, and (c) longitudinal relations between appropriate or non‐attuned mind‐related comments and baseline HRV or HRV decline at 4 and 12 months. Previous research has shown that appropriate and non‐attuned mind‐related comments are unrelated (e.g., Meins et al., 2003, 2012). Also, in the present study we did not find concurrent and longitudinal correlations between appropriate and non‐attuned comments at 4 and 12 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following pathways were modelled: (a) concurrent relations between baseline HRV and HRV decline during the stranger situation at 4 and 12 months (e.g., Izard et al., 1991; Porter et al., 1995), (b) concurrent relations between appropriate or non‐attuned mind‐related comments and baseline HRV or HRV decline at 4 and 12 months, and (c) longitudinal relations between appropriate or non‐attuned mind‐related comments and baseline HRV or HRV decline at 4 and 12 months. Previous research has shown that appropriate and non‐attuned mind‐related comments are unrelated (e.g., Meins et al., 2003, 2012). Also, in the present study we did not find concurrent and longitudinal correlations between appropriate and non‐attuned comments at 4 and 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…Mind‐mindedness is defined as parents’ tendency to treat their infant as a mental agent, and is assessed during infancy as parents’ tendency to comment appropriately or in a non‐attuned manner on their infant's putative internal states during free‐play situations (Meins, 1997; Meins et al., 2001). The appropriate and non‐attuned indices reflect two orthogonal dimensions of mind‐mindedness, unrelated to each other (Meins et al., 2003, 2012). Appropriate mind‐related comments indicate attunement to and validation of the infant's internal state.…”
Section: Introductionmentioning
confidence: 99%
“…Third, Vygotsky's concept of the zone of proximal development (Vygotsky 1934) provides a framework for understanding how sensitive input from caregivers can "scaffold" children's acquisition of mental state terms and concepts (Meins et al 2002). Fourth, Vygotsky's idea that language can be used as a psychological tool (Vygotsky 1930(Vygotsky /1978 in augmenting pre-existing cognitive capacities suggests that private and inner speech may play important roles in mediating children's own reflections on the nature of mental states and processes (Meins et al 2003). Finally, the Vygotskian notion of internalisation of semiotically mediated interpersonal activity (Vygotsky 1931(Vygotsky /1997 may prove useful for our theorising about how children's developing TOM abilities are rooted in their experience of social exchanges.…”
Section: More Than a Context For Learning? The Epistemic Triangle Andmentioning
confidence: 99%
“…Mind-mindedness is associated with a range of positive child outcomes. Higher levels of caregiver mind-mindedness in the first year of life are known to predict secure caregiver-child attachment (Arnott & Meins, 2007;Lundy, 2003;Meins et al, 2001; and superior performance on theory of mind tasks at ages 2 (Laranjo, Bernier, Meins, & Carlson, 2010) and 4 (Meins et al, 2002(Meins et al, , 2003). But mind-mindedness is unrelated to children's temperament (Meins, Fernyhough, Arnott, Turner, & Leekam, 2011) and general cognitive ability (e.g., Meins et al, 2001), suggesting that individual infant characteristics do not determine caregivers' mind-mindedness.…”
mentioning
confidence: 99%